Influence of new product development best practices on performance: an analysis in innovative Brazilian companies - Araujo, Tiago Ribeiro de [UNESP]; Jugend, Daniel [UNESP]; Pimenta, Marcio Lopes; Jesus, Gessica Mina Kim [UNESP]; Barriga, Gladys Dorotea Dorotea Cacsire [UNESP]; Toledo, José Carlos de; Mariano, Ari Melo (Emerald, 2021)
Purpose: This study aims to propose and test a research framework for analyzing the relationship between new product development (NPD) best practices and performance in companies that belong to innovative industries in Brazil. Design/methodology/approach: A quantitative survey was conducted, involving several industries, including agricultural machinery, automotive and pharmaceutical. Data was analyzed through multiple linear regression. Findings: Among the best practices investigated, the main results show that “innovative culture” and “project climate” are factors that significantly affect the performance of the NPD. Research limitations/implications: The choice of best practices can be considered a major limitation of this study, as this is a dynamic concept depending on a continuous analysis that must take into account the economic and technological environment. Practical implications: This study highlights a relationship between an innovative culture and performance. Some practices may be adopted to address an innovative culture, such as stimulating employee creativity, acceptance and partnership with external actors for the joint development of technologies and employee involvement with NPD. Originality/value: The findings expand the debate on best practices in NPD and innovation management by presenting results on the topic in an emerging country, in this case, Brazil.
Keywords: Best practices; Emerging markets; New product development; Product innovation